Principal Transformational Leadership and Teachers’ Motivation (Asian Education Studies, 2018)
This descriptive study aims to identify the relationship between the principal leadership and motivation among the national school teachers in the town of Nibong Tebal, Penang, Malaysia. A total of 283 teachers via random sampling method were chosen from twenty-one national school in the district of Seberang Perai Selatan, Penang. The questionnaires constructed by Leithwood and Jantzi (1999) and adapted by Anandan (2011) have been used to measure the principal transformational leadership. The questionnaire of Teacher Motivation Questionnaire by Chung (2012) was used to measure work motivation among teachers. The findings presented that the transformational leadership in the teacher's perspective is very high while the work motivational level among the teachers is high as well. The findings show that there are significant differences in both leadership style and teacher motivation towards teachers’ gender. Relationship analysis also indicated that there was a significant positive correlation between transformational leadership and teachers’ work motivation. Regression analysis also displayed that the best predictor of teachers’ motivation is the individual support in transformational leadership. In conclusion, this study recommends that principals should be competent in applying transformational leadership to improve teachers' innovation in accordance with the school suitability and the needs of the situation.